The differences in some motor skills among students involved in karate and football - Ajvaz Berisha; Afrim Koca; Kushtrim Berisha (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2019)
In theory and practice of every sport, and therefore also in the sport of Karate there are certain rules that must be respected in order to meet the desired goals. As a very important rule in the sport of karate is to start the physical exercising at the youngest age possible in order to stimulate the development of those motor skills which are specific to the sport. As for its implementation, this study has a transversal empirical character, which means that the measurements of the motor skills are done over a specific time period. The sample was defined as students of the age of 12 from the Middle School "Selami Hallaqi" Gjilan. In this research have been included 90 students, or two groups with 45 students each. The first group is consisted of students who except for the regular two hours per week of physical education classes have also exercised the sport of karate two more times a week, an hour a day. While, the second group is consisted of a student who besides the regular two times a week of physical education have also exercised football two more times, one hour per day. Measurements were made at the end of the school year. 9 motor variables were applied (Kurelić et al. 1975), running in 20 meters (MT20V), long jump from the place (MSKDM), high jump from the place (MSKVM), hand taping (MTRUK), leg walk ( MTNOG), eight with bowing(MOSPR), running sideways (mtrs) bowing ahead in the bank (MFLPRK), legs spread sideways-retaliation (MFLSP). For the processing of the result it was applied the analysis of t-test for independent samples. The basic statistical parameters of the results obtained in the two groups involved in the research show that the values obtained do not have an outlined asymmetry and incline to the lowest ones (hypo cortical). Analysis of the t-test for independent sample obtained shows that differences in all variables between groups were statistically significant. The changes obtained from the students involved in karate section show that specific exercises applied in the training of karate have helped to improve the moor tasks to a large extent, which is confirmed by a statistically significant difference between young karate sportsman and footballers (p <0.001). These results suggest that different educational technologies and through applying different training methods can be achieved different effects on motor latent space, which are confirmed in the research Šekeljič and Stamatovic, (2010).